Lexical Cohesion in Kid Talks: The Instagram Videos of Mila Stauffer - Dinda Amalia; Didin Nuruddin Hidayat (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2020)
This study aims to examine the use of lexical elements in kid talks. Mila Stauffer is a four-year-old celebrity who has four million followers on her Instagram account. Mila is known as a child who frequently shares her thoughts about particular topics, expressively, and comprehensively. The researchers are interested in Mila Stauffer because her Instagram videos have many viewers and comments. Numerous Instagram users also like her because she is different from the children that have the same age as her. In order to analyze Mila’s opinion about some topics through videos, lexical cohesion played an important role in the present study. To obtain an in-depth study of lexical cohesion, this study then analyzed ten Instagram videos with the available subtitle. The data of the study were collected through the Instagram account, Kcstauffer. The researchers applied a quantitative method in analyzing the lexical cohesion. Furthermore, the lexical cohesion analysis proposed by Halliday & Hasan has been used in the present study. The study revealed that, as analysed from Mila’s talk, there are differences between kids and adults in terms of the use of repetition. Further, repetition plays an important role in kids talk; one of which is to achieve cohesiveness in speaking. On the other hand, the least lexical cohesive devices used in a kid talk is superordinate.